Mechanism of Exogenous Jasmonic Acid-Induced Resistance to Thrips palmi in Hemerocallis citrina Baroni Revealed by Combined Physiological, Biochemical and Transcriptomic Analyses - Zhuonan Sun; Ning Ma; Ye Yang; Jun Wang; Nan Su; Hongxia Liu; Jie Li (Agronomy, 2024)
Jasmonic acid (JA) is a regulator of plant resistance to phytophagous insects, and exogenous JA treatment induces plant insect resistance. This study investigated the mechanism of exogenous JA-induced resistance of Hemerocallis citrina Baroni (daylily) to Thrips palmi at the biochemical and molecular levels. Daylily leaves sprayed with JA showed significantly higher levels of secondary metabolites—tannins, flavonoids, and total phenols, and activity of defense enzymes—peroxidase, phenylalanine ammonia lyase, polyphenol oxidase, and protease inhibitor (PI) than control leaves; the most significant effects were observed with 1 mmol L−1 JA. Owing to an improved defense system, significantly fewer T. palmi were present on the JA-treated plants than control plants. The JA-treated leaves had a smoother wax layer and fewer stomata, which was unfavorable for insect egg attachment. The differentially expressed genes (DEGs) were significantly enriched in insect resistance pathways such as lignin and wax biosynthesis, cell wall thickening, antioxidant enzyme synthesis, PI synthesis, secondary metabolite synthesis, and defense hormone signaling. A total of 466 DEGs were predicted to be transcription factors, mainly bHLH and WRKY family members. Weighted gene co-expression network analysis identified 13 key genes; TRINITY_DN16412_c0_g1 and TRINITY_DN6953_c0_g1 are associated with stomatal regulation and lipid barrier polymer synthesis, TRINITY_DN7582_c0_g1 and TRINITY_DN11770_c0_g1 regulate alkaloid synthesis, and TRINITY_DN7597_c1_g3 and TRINITY_DN1899_c0_g1 regulate salicylic acid and ethylene biosynthesis. These results indicate that JA treatment of daylily improved its resistance to T. palmi. These findings provide a scientific basis for the utilization of JA as an antagonist to control T. palmi in daylily.